(untitled) (Revista Rupturas, 2022)
The interactions between religion and politics are analyzed at two crucial moments during the development of the Cold War in Guatemala. The first one is that of the October Revolution 1944-1954 and the Counterrevolution, and the second one refers to the years when violence reached its peak during the civil war, specifically 1982-1983, when Efraín Ríos Montt ruled Guatemala. The way in which religion and politics intertwined at both moments had a significant impact on the ongoing disputes around state formation. The arrangements forged between religious elites and the State facilitated processes that established the presence and sociocultural influence of the Catholic Church from the first moment on and of the evangelical churches after the second.